Restoring Indigenous Names in Taxonomy - Gillman, LN; Wright, SD (Springer Nature, 2020)
Some pillars of scientific practice appear immutable. We propose that one of these needs more thorough consideration and modification: this being the long-standing emphasis in nomenclature for first published names over pre-existing indigenous names, in accepting species epithets. We suggest that biologists re-evaluate this practice, in the context of a current more general re-evaluation of indigenous knowledge. We propose that it is now time to critically examine taxonomic protocols in favour of both assigning and reinstating indigenous names whenever possible.
Keywords: Plant sciences; Scientific community; Zoology